Factors that influence early breastfeeding of singletons and twins in Korea: a retrospective study. Issue 1 (December 2016) - Kim, Bo-Yeoul
Abstract Background This study aimed to evaluate the factors that influence breastfeeding throughout the hospital stay, including prenatal preparation, early skin-to-skin contact directly after delivery, rooming-in, feeding before the first breastfeed, time to first breastfeed, and postpartum support. This study also aimed to verify whether these factors were significant after adjusting for the mother's characteristics, the newborn's characteristics, and the delivery characteristics. Methods A retrospective survey was used to collect the data. Factors that influenced breastfeeding throughout the hospital stay, and differences between the types of newborns were analyzed. Results Among twins, a higher likelihood of breastfeeding throughout the hospital stay was associated with not feeding before the first breastfeeding and an earlier start time for the first breastfeeding. Among singletons, a higher likelihood of breastfeeding throughout the hospital stay was associated with early skin-to-skin contact, no other feeding before the first breastfeed, and an earlier commencement of the first breastfeed. Conclusions Effort should encourage early breastfeeding, without restriction, to improve the breastfeeding rate among mothers of twins. Moreover, an individualized approach that addresses the factors that influence breastfeeding for each type of newborn may help improve the corresponding rates of breastfeeding throughout the hospital stay.